Feasibility of energy-resolved dose imaging technique in pencil beam scanning mode. (29th September 2020) - Alaka, B G; Bentefour, El H; Chirvase, Cezarina; Samuel, Deepak; Teo, Boon-Keng Kevin
Abstract: Purpose: Proton energy-resolved dose imaging (pERDI) is a recently proposed technique to generate water equivalent path length (WEPL) images using a single detector. Owing to its simplicity in instrumentation, analysis and the possibility of using the in-room x-ray flat panels as detectors, this technique offers a promising avenue towards a clinically usable imaging system for proton therapy using scanned beams. The purpose of this study is to estimate the achievable accuracy in WEPL and Relative Stopping Power (RSP) using the pERDI technique and to assess the minimum dose required to achieve such accuracy. The novelty of this study is the first demonstration of the feasibility of pERDI technique in the pencil beam scanning (PBS) mode. Methods: A solid water wedge was placed in front of a 2D detector (Lynx). A library of energy-resolved dose functions (ERDF) was generated from the dose deposited in the detector by 50 PBS layers of energy varying from 100 MeV to 225 MeV. This set-up is further used to image the following configurations using the pERDI technique: stair-case shaped solid water phantom (configuration 1), electron density phantom (configuration 2) and head phantom (configuration 3). The result from configuration 1 was used to determine the achievable WEPL accuracy. The result from configuration 2 was used to estimate the relative uncertainty in RSP. Configuration 3 was used to evaluate the effect of range mixing on the WEPL. In all three cases, the variation of the accuracy with respect to dose, by varying the number of scanning layers, was also studied. Results: An accuracy of 1 mm in WEPL was achieved using the Lynx detector with an imaging field of 10 PBS layers or more, which is equivalent to a total dose of 5 cGy. The RSP is measured with a precision better than 2% for all homogeneous inserts of tissue surrogates. The pERDI technique failed for tissues surrogates with total WEPL outside the calibration window (WEPL < 70 mm) like in the case of lung exhale and lung inhale. The imaging of an anthropomorphic head phantom, in the same condition, produced a WEPL radiograph and compared to the WEPL derived from CT using gamma index analysis. The gamma index failed in the heterogeneous areas due to range mixing. Conclusions: The pERDI technique is a promising clinically usable imaging modality for reducing range uncertainties and set-up errors in proton therapy. The first results have demonstrated that WEPL and RSP can be estimated with clinically acceptable accuracy using the Lynx detector. Similar accuracy is also expected with in-room flat-panel detectors but at significantly reduced imaging dose. Though the issue of range mixing is still to be addressed, we expect that a statistical moment analysis of the ERDFs can be implemented to filter out the regions with high gradient of range mixing.